Hemorrhagic stroke following viper bites and delayed antivenom administration: three case reports from the Western Brazilian Amazon - Aline Stephanie Pérez-Gómez; Wuelton Marcelo Monteiro; Guilherme Augusto Pivoto João; Jose Diego de Brito Sousa; Izabella Picinin Safe; Marcia Melo Damian; Jacqueline Almeida Gonçalves Sachett; Iran Mendonça da Silva (Revista da Sociedade Brasileira de Medicina Tropical)
Abstract Snakebites were included by the World Health Organization in their list of neglected diseases. In Latin America, most snakebites are caused by species of the Viperidae family, notably by the genus Bothrops. Bothrops atrox accounts for 90% of the cases of envenoming in the Brazilian Amazon. In this report, we present a series of three cases of snakebites that evolved with hemorrhagic stroke due to delays in the access to antivenom in the Brazilian Amazon, being fundamental for diagnosis to validate the clinical suspicion and make decisions that would improve the treatment and prognosis of the patients.